Situated Learning and On-Farm Apprenticeships: Political Implications of Negotiating Apprentice Identity - Lorien E. MacAuley; Kim L. Niewolny (Adult Education Research Conference, 2015)
By drawing upon the tradition of situated and activity perspectives of adult learning, this mixed methods study underscores the sociocultural and politicized processes by which farmer/learners negotiate apprentice identity. Our findings offer implications for the formation of equitable apprenticeship learning experiences and career pathways.
Keywords: apprenticeship; identity; situated learning